What it takes to reduce sitting at work: a pilot study on the effectiveness and correlates of a multicomponent intervention - Porath, Jannik; Schmidt, Laura; Möckel, Juliane; Dold, Chiara; Hennerkes, Lisa; Haussmann, Alexander (International archives of occupational and environmental health, 2024)
This study aimed to assess the feasibility and effects of a simple-to-implement multicomponent intervention to reduce sedentary time of office workers.